Development of autonomous radiation mapping robot - Zakaria, Abd Hafiz; Mohd Mustafah, Yasir; Abdullah, Jaafar; Alang Rashid, Nahrul Khair; Abdullah, Taufiq (Elsevier BV, 2017)
This paper discusses the development of a spatial radiation map by an autonomous mobile robot that is equipped with Geiger Muller sensor. Mapping of gamma radiation autonomously using robot as agents will help to prevent harm to human especially when radiation related disaster occur. Hence, we intend to develop a gamma radiation mapping system that reads and process location data of a mobile robot with encoder as well as the radiation data transmitted by the Geiger Muller sensor on the mobile robot. A grid based algorithm was develop to build the radiation map. The system was then tested under several conditions. The results of the spatial distribution map with respect to respective waypoints were discussed at the end of this paper.